2010
DOI: 10.1128/jcm.01306-10
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Version 2.0 of the Cobas AmpliPrep/Cobas TaqMan Real-Time PCR Assay for Hepatitis B Virus DNA Quantification

Abstract: The detection and quantification of hepatitis B virus (HBV) DNA are essential for the diagnosis and treatment of chronic HBV infection. The use of real-time PCR assays for HBV DNA quantification is strongly recommended. The goal of this study was to evaluate the intrinsic characteristics and clinical performance of version 2.0 (v2.0) of the Cobas AmpliPrep/Cobas TaqMan (CAP/CTM) assay, a fully automated platform for HBV DNA quantification in serum or in plasma with a claimed lower limit of detection of 20 IU/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 12 publications
1
43
2
1
Order By: Relevance
“…This study is the first to simultaneously compare the performance of these three assays and corroborates prior reports of the performance of CAP/CTM (3,4,6), HP (3,11), and TNAI (10). Sensitivities were similar, with HP and TNAI slightly more sensitive than CAP/CTM in the study, and the sensitivity of the CAP/ CTM assay closely matched previously reported results (6).…”
Section: Discussionsupporting
confidence: 85%
“…This study is the first to simultaneously compare the performance of these three assays and corroborates prior reports of the performance of CAP/CTM (3,4,6), HP (3,11), and TNAI (10). Sensitivities were similar, with HP and TNAI slightly more sensitive than CAP/CTM in the study, and the sensitivity of the CAP/ CTM assay closely matched previously reported results (6).…”
Section: Discussionsupporting
confidence: 85%
“…Serum levels of ALT, creatinine, phosphorus, HBV DNA, HBeAg, and anti-hepatitis B e antibody were assessed for all patients every 2 to 3 months. Serum HBV DNA levels were measured at baseline and each follow-up visit using either Roche COBAS TaqMan (lower limit of detection, 20 IU/ml; Roche Molecular Systems, Branchburg, NJ) or Abbott m2000 (lower limit of detection, 15 IU/ml; Abbott Diagnostics, Chicago, IL) (20). At baseline, testing for genotypic resistance, which was defined as the detection of HBV variants with substitutions conferring antiviral drug resistance, was performed for all study patients and was repeated for patients who experienced virologic breakthrough during the treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory measurements were assessed for all patients, including serum levels of ALT, creatinine, and HBV DNA and hepatitis B e antigen (HBeAg) and antibody (anti-HBe Ab) every 2 to 3 months. At baseline and at each follow-up visit, serum HBV DNA levels were quantified using the Cobas AmpliPrep/Cobas TaqMan version 2.0 assay (Roche Molecular System, Branchburg, NJ), which has a dynamic range of quantification of 20 to 1.7 ϫ 10 8 IU/ml (1.3 to 8 log 10 IU/ml) (16). HBeAg and anti-HBe Ab were determined using a radioimmunoassay (RIA Elisa Rapid kit; Shin Jin Medics, Seoul, Republic of Korea).…”
Section: Methodsmentioning
confidence: 99%